Analysis of electricity consumption in Andalusia during the year 2020 - Ceballos-González, Manuel; Torres-Chacón, Javier Antonio (Revista de Estudios Andaluces, 2023)
The main goal of this paper is to develop a statistical study about the electricity consumption in every city and town of Andalusia which has Endesa Distribución Eléctrica as supplier during the year 2020. In order to do so, we will use Stata software and the database of the Mutiterritorial Information System of Andalusia. The results obtained allow us to conclude that there exist significant differences in Andalusia with respect to the average electricity consumption per capita locally and globally. This yields to the existence of atypical data and that our variable does not fit to a normal behavior. We have also concluded that there exists a strong correlation with other five variables from the database.